Melatonin stabilizes rupture‐prone vulnerable plaques via regulating macrophage polarization in a nuclear circadian receptor RORα‐dependent manner. Issue 2 (14th May 2019) - Ding, Song; Lin, Nan; Sheng, Xincheng; Zhao, Yichao; Su, Yuanyuan; Xu, Longwei; Tong, Renyang; Yan, Yang; Fu, Yanan; He, Jie; Gao, Yu; Yuan, Ancai; et al.
Abstract: Rupture of vulnerable plaques is the main trigger of acute cardio‐cerebral vascular events, but mechanisms responsible for transforming a stable atherosclerotic into a vulnerable plaque remain largely unknown. Melatonin, an indoleamine hormone secreted by the pineal gland, plays pleiotropic roles in the cardiovascular system; however, the effect of melatonin on vulnerable plaque rupture and its underlying mechanisms remains unknown. Here, we generated a rupture‐prone vulnerable carotid plaque model induced by endogenous renovascular hypertension combined with low shear stress in hypercholesterolemic ApoE −/− mice. Melatonin (10 mg/kg/d by oral administration for 9 weeks) significantly prevented vulnerable plaque rupture, with lower incidence of intraplaque hemorrhage (42.9% vs. 9.5%, P  = 0.014) and of spontaneous plaque rupture with intraluminal thrombus formation (38.1% vs. 9.5%, P  = 0.029). Mechanistic studies indicated that melatonin ameliorated intraplaque inflammation by suppressing the differentiation of intraplaque macrophages toward the proinflammatory M1 phenotype, and circadian nuclear receptor retinoid acid receptor‐related orphan receptor‐α (RORα) mediated melatonin‐exerted vasoprotection against vulnerable plaque instability and intraplaque macrophage polarization. Further analysis in human monocyte‐derived macrophages confirmed the role of melatonin in regulating macrophage polarization by regulating the AMPKα‐STATs pathway in a RORα‐dependent manner. In summary, our data provided the first evidence that melatonin‐RORα axis acts as a novel endogenous protective signaling pathway in the vasculature, regulates intraplaque inflammation, and stabilizes rupture‐prone vulnerable plaques.